2003
DOI: 10.1034/j.1600-079x.2003.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin increases oestradiol‐induced bone formation in ovariectomized rats

Abstract: : To assess the effect of melatonin on bone metabolism in ovariectomized rats, receiving oestradiol therapy or not, melatonin was administered in the drinking water (25 μg/mL water) and oestradiol (10 μg/kg body weight) or vehicle was given subcutaneously 5 days/week for up to 60 days after surgery. Urinary deoxypyridinoline (a marker of bone resorption) and circulating levels of bone alkaline phosphatase activity (a marker of bone formation), as well as serum calcium and phosphorus levels, were measured every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
82
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 39 publications
10
82
0
3
Order By: Relevance
“…Moreover, we were the first to find that melatonin, a major hormonal product of the pineal gland, functioned negatively in both osteoclasts and osteoblasts [18]. The action of melatonin on bone has also subsequently been reported in in vivo studies in the rat [23]. Moreover, we indicated that osteogenesis in the regenerating scale is very similar to that seen in mammalian membranous bone and that regenerating scales have estrogen receptors which respond to estrogen in the same manner as mammalian osteoblasts [24].…”
Section: Introductionmentioning
confidence: 78%
“…Moreover, we were the first to find that melatonin, a major hormonal product of the pineal gland, functioned negatively in both osteoclasts and osteoblasts [18]. The action of melatonin on bone has also subsequently been reported in in vivo studies in the rat [23]. Moreover, we indicated that osteogenesis in the regenerating scale is very similar to that seen in mammalian membranous bone and that regenerating scales have estrogen receptors which respond to estrogen in the same manner as mammalian osteoblasts [24].…”
Section: Introductionmentioning
confidence: 78%
“…It has a variety of physiological actions such as control of circadian rhythm, sexual development, inflammation and hormone secretion (3,8,10,13,15). Melatonin promotes osteoblast differentiation and bone formation (38,39), and can protect the oral cavity from tissue damage (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, melatonin regulates various physiological and pathophysiological processes such as control of body temperature, sexual development, inflammation, the immune reponse and cell proliferation (8)(9)(10)(11)(12)(13). Melatonin also regulates bone remolding, prevents osteoporosis, and induces dentine formation and osseointegration of dental implants (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…The investigation and applications of melatonin in the hard tissues, bone and tooth, have received great attention. Melatonin has been investigated relative to bone remolding osteoporosis, osseointegration of dental implants and dentine formation Ladizesky et al, 2003;Cutando et al, 2007Cutando et al, , 2008Kotlarczyk et al, 2012;Liu et al, 2013). Osteopontin is one of the major non-collagen proteins in extracellular bone matrix, it has a role in osteoclast-mediated bone resorption.…”
Section: Introductionmentioning
confidence: 99%